Humanizing Digital Reality Design Modelling Symposium Paris 2017 (Springer Singapore, 2018)
This book aims at finding some answers to the questions: What is the influence of humans in controlling CAD and how much is human in control of its surroundings? How far does our reach as humans really go? Do the complex algorithms that we use for city planning nowadays live up to their expectations and do they offer enough quality? How much data do we have and can we control? Are today's inventions reversing the humanly controlled algorithms into a space where humans are controlled by the algorithms? Are processing power, robots for the digital environment and construction in particular not only there to rediscover what we already knew and know or do they really bring us further into the fields of constructing and architecture? The chapter authors were invited speakers at the 6th Symposium "Design Modelling Symposium: Humanizing Digital Reality", which took place in Ensa-Versailles, France from 16 - 20 September 2017. .